2017
DOI: 10.1001/jamacardio.2017.3574
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Clinical Characteristics and Outcomes of Peripartum Cardiomyopathy Between African American and Non–African American Women

Abstract: In a large cohort of women with well-phenotyped PPCM, this study demonstrates a different profile of disease in African American vs non-African American women. Further work is needed to understand to what extent these differences stem from genetic or socioeconomic differences and how treatment of African American patients might be tailored to improve health outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
94
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 133 publications
(98 citation statements)
references
References 19 publications
2
94
1
1
Order By: Relevance
“…Africans and African Americans are at a higher risk for developing PPCM, with an estimated incidence of 1:100 pregnancies in Nigeria and 1:299 in Haiti whereas incidences in Caucasian populations range from 1:1500 pregnancies in Germany to 1:10 000 in Denmark . In a large US cohort of well‐phenotyped patients, African American women were diagnosed with PPCM at a younger age and later in the postpartum period, and were more likely to present with a LVEF < 30% compared with non–African American women . In the USA, an increasing incidence was described over the past years .…”
Section: Definition and Epidemiologymentioning
confidence: 99%
“…Africans and African Americans are at a higher risk for developing PPCM, with an estimated incidence of 1:100 pregnancies in Nigeria and 1:299 in Haiti whereas incidences in Caucasian populations range from 1:1500 pregnancies in Germany to 1:10 000 in Denmark . In a large US cohort of well‐phenotyped patients, African American women were diagnosed with PPCM at a younger age and later in the postpartum period, and were more likely to present with a LVEF < 30% compared with non–African American women . In the USA, an increasing incidence was described over the past years .…”
Section: Definition and Epidemiologymentioning
confidence: 99%
“…Comparison between PPCM collectives of different ethnic backgrounds suggests that African PPCM patients may have a different pathophysiology and a lower chance for full recovery, compared with non‐African patients, but a direct comparison of different ethnic cohorts has not been performed yet. Thus, we aimed to directly compare the outcome of two large PPCM registries, one with patients from South Africa (SA‐PPCM), including only patients of African ethnicity, and one from Germany (G‐PPCM), with only Caucasian patients included.…”
Section: Introductionmentioning
confidence: 99%
“…In the IPAC cohort, mean LVEF at 12 month follow-up was 47% for black women and 56% for non-black women (P=0.001), and 16 of 27 black women recovered LVEF ≥50% compared with 50 of 65 non-black women (P=0.13) 76. Similarly, in a recent series of 220 women, black women were more likely than non-black women to present with LVEF <30% at diagnosis (56.5% v 39.5%; P=0.03) and were more likely to worsen after diagnosis (35.3% v 18.4%; P=0.02) despite similar use of medication in both groups 77. Although rates of adverse clinical events (such as death and cardiac transplantation) in most contemporary studies are sufficiently low that significant differences between racial groups are not apparent, one recent study of 52 black women and 104 non-black women showed higher rates of death or transplantation in black women (P=0.03) 96.…”
Section: Natural Course and Prognosismentioning
confidence: 81%
“…Recent data suggest that 50-80% of women with PPCM recover to normal range left ventricular systolic function (LVEF ≥50%), with most of this recovery occurring within the first six months 3767788. These statistics reflect the great improvement in the prognosis of PPCM since the early 1970s, when reported mortality was 30-50% (table 3).…”
Section: Natural Course and Prognosismentioning
confidence: 96%